2021
DOI: 10.1093/bbb/zbaa090
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG12 downregulates RAGE to attenuate hypoxia-reoxygenation-induced apoptosis in H9c2 cells

Abstract: Ischemia-reperfusion (I/R) injury causes cardiac dysfunction through several mechanisms including the irregular expression of some long noncoding RNA. However, the role of SNHG12 in myocardial I/R injury remains unclear. Here, we found the increase of the SNHG12 level in hypoxia-reoxygenation (H/R)-injured-H9c2 cells. SNHG12 silencing enhanced the apoptosis of H/R-injured H9c2 cells, while SNHG12 overexpression relieved the cardiomyocyte apoptosis induced by H/R stimulation. Additionally, the suppression of SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…In addition to cancer, SNHG12 has been shown to be involved in cerebral ischemia-reperfusion (I/R) injury; specifically, its upregulation protects against cerebral I/R injury ( 21 ). Recently, Lu et al pointed out that the lncRNA SNHG12 is effective in protecting against hypoxia/reoxygenation-induced injury in myocardial cells ( 22 ). Furthermore, SNHG12 is a kind of snoRNAs, and these snoRNAs were predicted to have roles in post-translational modifications and alternative splicing, processes differentially regulated in HCM ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cancer, SNHG12 has been shown to be involved in cerebral ischemia-reperfusion (I/R) injury; specifically, its upregulation protects against cerebral I/R injury ( 21 ). Recently, Lu et al pointed out that the lncRNA SNHG12 is effective in protecting against hypoxia/reoxygenation-induced injury in myocardial cells ( 22 ). Furthermore, SNHG12 is a kind of snoRNAs, and these snoRNAs were predicted to have roles in post-translational modifications and alternative splicing, processes differentially regulated in HCM ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 Numerous studies have elaborated the essential functions of SNHG12 in human diseases, including atherosclerosis, 29 cerebral I/R injury, 30 and I/R-induced cardiac dysfunction. 31 Besides, Wu et al revealed that SNHG12 could relieve cerebral I/R injury by activating SIRT1/FOXO3a signaling through inhibition of autophagy and oxidative stress. 32 In addition, Yuan et al disclosed that SNHG12 promoted cell proliferation and reduced cell apoptosis in breast cancer via regulating the miR-15a-5/SALL4 cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al revealed that ZFAS1 attenuated BV-induced neurotoxicity via the miR-421/ZNF564 pathway 28. Numerous studies have elaborated the essential functions of SNHG12 in human diseases, including atherosclerosis,29 cerebral I/R injury,30 and I/Rinduced cardiac dysfunction 31. Besides, Wu et al revealed that SNHG12 could relieve cerebral I/R injury by activating…”
mentioning
confidence: 99%
“…In AGEs-induced endothelial cells, lncRNA MEG3 regulated cell viability, proliferation, and apoptosis through the lncRNA MEG3/MiR-93/p21 mediated pathway during the onset of diabetic vascular diseases [ 97 ]. In a cell-based study on hypoxia/reoxygenation-injured cardiomyocytes, lncRNA SNHG12 down-regulated RAGE, NF-κB expression, and pro-inflammatory responses [ 102 ]. In a different context, the lncRNA TP73-AS1-mediated RAGE-HMGB1 signaling pathway upregulated NF-κB expression and pro-inflammatory cytokine levels [ 12 , 103 ].…”
Section: Understanding the Role Of Lncrnas In Ages-related Dnmentioning
confidence: 99%